(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The virtual labs and simulation integration with the physics courses gives enormous potential to change the gap between the theoretical underpinnings and the real-life application of the knowledge in order to get a deeper insight and experience. This paper discusses how these technologies are effective in improving the feasibility of physics in post-primary and in tertiary education. The study evaluates the involvement of the use of virtual tools in overcoming the challenges encountered by teachers within this sector that include resource issues, lack of student interest, and unavailability of practical experimentation through a thorough synthesis of secondary literature in the form of peer-reviewed studies, education reports, and case studies published between 1970 and 2025. Among the major discoveries are that virtual laboratories enhance conceptual mastery by as much as 30 percent and make students more motivated, especially when the under-resourced environment is considered. The review identifies the weaknesses of conventional laboratory practices and suggests ways to address the limitations such as the training of teachers and access to technology. This work sheds light on the role of simulations in inquiry based learning that can be applied by teachers and policy makers to streamline physics education in an ever-changing, technology-focused world.